Obtaining of Granulated Gypsum Anhydrite on the Basis of Technogenic Wastes of Chemical and Metallurgical Complex for Use in Portland Cement Production - Ponomarenko, Alexander (KnE Materials Science, 2020)
The composition and properties of fluorine–anhydrite and steel–refining slag which are wastes of production of hydrogen fluoride and steel were determined. It is established that fluorine–anhydrite of the current output does not meet the requirements to materials for the production of Portland cement. Therefore to improve the technical and consumer properties of fluorine-anhydrite (for increasing the amount of CaSO4 ⋅2H2O and neutralization of H2SO4) the studies of its’ conditioning processes with steel– refining slag were carried out. It was found that the mass transfer coefficient of sulfuric acid through the capillary and the degree of its neutralization by slag depend on the dispersion of fluorine–anhydrite, its porosity and initial acidity. The most effective binding of sulfuric acid occurs with the introduction of slag in stoichiometric amounts, the size of fluorine–anhydrite granules up to 20 mm and a processing time of 60 minutes. After storage in air-humid conditions for 12 hours of fluorine–anhydrite treated with slag the strength of its granules, the amount of dihydrate gypsum and toxicological properties meet the requirements. Keywords: techno–gypsum, refining slag, neutralization, conditioning, gypsum stone, Portland cement